Impact of Ramadan Fasting in People with Type 1 Diabetes and Diabetic Kidney Disease: Insights from the DaR Global Survey - Afandi, Bachar; Odhaib, Samih Abed; Habib, Mohamed; Aljohani, Naji; Ahmedani, Muhammad Yaqoob; Elbarbary, Nancy; Alfadhli, Eman; Kallash, Majd Aldeen; Hassanein, Mohamed (Journal of Diabetes and Endocrine Practice, 2025)
Despite the scarcity of data, individuals with type 1 diabetes mellitus (T1D) and diabetic kidney disease (DKD) are considered at moderate to high risk for Ramadan fasting and are individually advised against fasting.This subgroup analysis of the Diabetes and Ramadan (DaR) global survey was conducted to evaluate the outcomes and characteristics of patients with T1D complicated by DKD who observe fasting and to compare their outcomes with those of fasting people living with T1D uncomplicated by DKD.Using a specifically designed SurveyMonkey questionnaire, Muslim individuals with T1D and DKD were surveyed in several countries from different geographical regions and compared statistically to people with T1D without DKD or associated comorbidities.Note that 53.8% (N = 86) of individuals with T1D and DKD fasted during Ramadan in comparison with 74% (N = 1,523) of the control group. Those with DKD experienced higher rates of hypoglycemia (65.1%) and hyperglycemia (69.6%) than the control group (56.5 and 42.5%, respectively). They also had more frequent emergency visits and hospitalizations. Additionally, among individuals with T1D and DKD, nonfasters exhibited significant differences in biochemical markers and demographics compared with those who fasted.Individuals with T1D and DKD are generally older, have multiple diabetes-related complications, and are less likely to fast during Ramadan. For those who do fast, the risks are significant, including higher rates of hypoglycemia and hospital admissions compared with the control group. Ensuring safe fasting in this population requires interdisciplinary collaboration, patient education, and expert medical guidance.
Keywords: Ramadan fasting; type 1 diabetes mellitus; diabetic kidney disease; hypoglycemia; hyperglycemia; diabetes education; self-monitoring of blood glucose; risk stratification